2020
DOI: 10.1002/lom3.10358
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised biodiversity estimation using proteomic fingerprints fromMALDI‐TOF MSdata

Abstract: Species identification using matrix assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) data strongly relies on reference libraries to differentiate species. Because comprehensive reference libraries, especially for metazoans, are rare, we explored the accuracy of unsupervised diversity estimations of communities using MALDI-TOF MS data in the absence of reference libraries to provide a method for future application in ecological research. To discover the best analysis strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The intercomparison of MOTUs and POTUs revealed that 7% of specimens were assigned differently. A slightly smaller error rate of 4% has been observed applying clustering on simulated data sets (Rossel and Martínez Arbizu, 2020). Misidentification of single specimens was neither detectable using a direct comparison of sample distances nor by consensus clustering, indicating that misidentification is probably caused by variance in the proteomic profiles.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The intercomparison of MOTUs and POTUs revealed that 7% of specimens were assigned differently. A slightly smaller error rate of 4% has been observed applying clustering on simulated data sets (Rossel and Martínez Arbizu, 2020). Misidentification of single specimens was neither detectable using a direct comparison of sample distances nor by consensus clustering, indicating that misidentification is probably caused by variance in the proteomic profiles.…”
Section: Discussionmentioning
confidence: 87%
“…Yet, no gold standard for unsupervised species delimitation has been developed. A previous study successfully applied partitioning around medoids (PAM) clustering in combination with the silhouette index to predict species number (Rossel and Martínez Arbizu, 2020). PAM and also k‐means clustering were not applicable to our study due to the expected unbalanced data set with most probably many singletons and small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, DNA sequences and MALDI‐TOF libraries can be simultaneously generated by splitting specimens (if their size allows this) into multiple pieces using some for genomic and some for proteomic fingerprinting (Rossel and Arbizu 2018; Rossel et al 2019; Rossel and Martínez Arbizu 2019). If no libraries for a region are available at all, automatic biodiversity estimation based on a clustering analysis and automatic cluster recognition can be performed (Rossel and Martínez Arbizu 2020) to allow biodiversity comparisons of different investigated areas. A combination of both approaches can be used for areas with an incomplete reference library.…”
Section: Proteomic Fingerprinting By Maldi‐tof Msmentioning
confidence: 99%